Methylenetetrahydrofolate reductase gene polymorphism in endometrial cancer: A systematic review and meta-analysis - Xian-jun Wang; Li-hui Xu; Yue-ming Chen; Li Luo; Qiao-feng Tu; Jin Mei (Elsevier, 2015)
Objective: We conducted a meta-analysis of case-controlled prospective or retrospective studies to assess the effect of MTHFR polymorphisms on the risk of developing endometrial cancer. Materials and methods: PubMed, Cochrane, EMBASE, and ISI Web of Knowledge were searched (up to March 2014) for prospective or retrospective case-controlled studies that investigated the association of three MTHFR polymorphisms (rs180113 [C677T], rs1801131 [A1289C], and rs2274976 [G1793A]) with endometrial cancer. Results: The patient population included subjects from three separate countries: China, Spain, and the USA. Only one study reported quantitative findings for MTHFR G1793A and, consequently, this polymorphism was not evaluated in our analysis. There were no significant associations of any MTHFR C677T or MTHFR A1298C alleles or genotypes with endometrial cancer (all p > 0.300). Conclusion: This meta-analysis does not support the association of endometrial cancer with two common MTHFR polymorphisms from this patient population.